Evaluation of the Cost – Effectiveness of Cutaneous Leishmaniasis Treatment after the Earthquake in Bam - M.R Aflatoniyan; I SHarifi; A.R Fekri (Journal of Kerman University of Medical Sciences, 2009)
Background & Aims: Cutaneous leishmaniasis (CL) is a vector – borne disease and at present it is one of the important health problems in tropical and sub - tropical countries including Iran. Due to imposed expenses to the people and government, this study was performed to evaluate the cost – effectiveness of cutaneous leishmaniasis treatment in the years after the earthquake in Bam/Iran. Methods: In a descriptive cross-sectional study data about treatment costs CL-patients during 2006-7 were collected. Overall, 100 recovered patients were randomly selected and their treatment costs were analyzed. Results: For 5320 CL patients about 2570 million rials was spend by the government that was equal to per capita cost of 483676 rials. In addition, 1150 million rials were spent by the patients themselves in private clinics which increase the per capita cost to 216320 rials. Overall, 3% of the patients referred to private sectors that had 2 million rials costs and 25% referred to both governmental and private sectors which has led to a per capita cost of 550000 rials. In total, over 90% of the costs were direct and 10% were indirect costs. Conclusion: The per capita treatment cost in this study shows a significant difference with those by other national and international reports. The establishment of CL Treatment Center after the earthquake in bam has reduced the disease costs and provided an efficient, free and easy accessible service for the patients. This experience could be a suitable model to be used nationally as well as globally